2020
DOI: 10.1016/j.ijdrr.2020.101845
|View full text |Cite
|
Sign up to set email alerts
|

How is COVID-19 pandemic impacting mental health of children and adolescents?

Abstract: The coronavirus disease (COVID-19) affected virtually all countries. Uncertain about the health risk and an increasing financial loss will contribute to widespread emotional distress and an increased risk of psychiatric disorders shortly. Posttraumatic, anxiety, and depression disorders are expected during and aftermath of the pandemic. Some groups, like children, have more susceptibility to having long term consequences in mental health. Herein, we made a comprehensive and non-systematic search in four databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
530
6
44

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 623 publications
(610 citation statements)
references
References 65 publications
(190 reference statements)
30
530
6
44
Order By: Relevance
“…A recent review (Brooks et al, 2020) suggested that quarantine measures may lead to feelings of boredom and anger, which may affect both parents and adolescents. For adolescents, feelings of loneliness during the lockdown in combination with the possibility that they receive less peer support because of social distancing, may place them at risk for other mental health problems such as depressive symptoms or (social) anxiety (Loades et al, 2020;Marques de Miranda et al, 2020). Negative feelings in families may spill over from adolescents to parents and to the quality of their interaction (Van Eldik et al, 2020;Keijsers et al, 2016).…”
Section: Covid-19 and Parent-adolescent Relationshipsmentioning
confidence: 99%
“…A recent review (Brooks et al, 2020) suggested that quarantine measures may lead to feelings of boredom and anger, which may affect both parents and adolescents. For adolescents, feelings of loneliness during the lockdown in combination with the possibility that they receive less peer support because of social distancing, may place them at risk for other mental health problems such as depressive symptoms or (social) anxiety (Loades et al, 2020;Marques de Miranda et al, 2020). Negative feelings in families may spill over from adolescents to parents and to the quality of their interaction (Van Eldik et al, 2020;Keijsers et al, 2016).…”
Section: Covid-19 and Parent-adolescent Relationshipsmentioning
confidence: 99%
“…The pandemic has resulted in the disruption of the daily routines of everyone including children, adolescents, and young adults. [1][2][3][4][5][6][7] Attending in-person school, physical exercise, social interactions, nutrition, screen time, family meal time, bedtime schedules, and quality of sleep are daily routines that have all been significantly disrupted. The relative impact of these disruptions and the child's response to this stress is dependent on the child's developmental stage.…”
Section: Children's and Families' Behavioral And Mental Health Duringmentioning
confidence: 99%
“…5 Other important factors include socioeconomic status; status of the intactness of the family; family stresses; access to technology for remote education and social interactions; nutritional status; presence of underlying chronic illness and/or mental or behavioral health problems; and access to medical, social, and psychological/psychiatric services. [1][2][3][4][5][6][7] The mental health responses to these stressors include high rates of depression, anxiety, and posttraumatic symptoms among the children. 5 Other distresses include neglect and abuse, family disruption, isolation, and loneliness.…”
Section: Children's and Families' Behavioral And Mental Health Duringmentioning
confidence: 99%
See 2 more Smart Citations